Internalizing Qawlan Ethics Through the Living Qur’an: A Study Among Santriwati at Dayah Al-Muslimun, Aceh - Chalis, M.; Nurkhalis, Nurkhalis; Juwaini, Juwaini; Mawaddah, Nurul; Rizqiy, Muhammad (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2025)
Communication plays a vital role in shaping the ethical and spiritual character of santriwati (female students at Islamic boarding schools). This study explores the internalization of Qur’anic communication principles—qawlan layyīna (gentle speech), qawlan karīmā (noble speech), and qawlan ma’rūfā (appropriate speech)—within the lived experiences of santriwati at Dayah Terpadu Al-Muslimun in Aceh, Indonesia. Employing a qualitative descriptive approach grounded in phenomenology, data were collected through participant observation, semi-structured interviews, and documentation, and analyzed thematically using Miles and Huberman’s model. Findings indicate that santriwati’s understanding of qawlan is shaped more by social experience and role modeling than by textual memorization. These principles are practiced adaptively in both hierarchical and peer interactions and contribute to the formation of moral resilience, communicative empathy, and Islamic identity. The study affirms that qawlan functions as a form of living moral grammar—an embodied ethical structure that regulates speech, intention, and social behavior in and beyond the dayah. This research extends the framework of the Living Qur’an from normative interpretation to performative praxis and offers a theoretical and practical foundation for developing Qur’anic-based communication ethics curricula responsive to the challenges of the digital era.